Ghost Town Living: Presenting the Past on YouTube - (:unkn) unknown (My University, 2023)
Cerro Gordo is a privately-owned historic mining town in California, and the YouTube channel Ghost Town Living, with over 1.6 million followers, documents the current owner's goal of preserving and restoring the town for visitation. This thesis explores how Cerro Gordo and Ghost Town Living can be understood together through the lenses of museology, digital anthropology, and archaeology. Based on a site visit, analysis of digital media, and interviews with staff and people connected to the site, I explore the intersection between heritage sites and social media, and more widely, changing perceptions of American heritage, including who has the right to shape those perceptions and who may lay claim to them.
Keywords: American Heritage; Cerro Gordo; Ghost Town; Mining Town; Museology; YouTube